2021
DOI: 10.1038/s41467-021-27075-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct conformations of the HIV-1 V3 loop crown are targetable for broad neutralization

Abstract: The V3 loop of the HIV-1 envelope (Env) protein elicits a vigorous, but largely non-neutralizing antibody response directed to the V3-crown, whereas rare broadly neutralizing antibodies (bnAbs) target the V3-base. Challenging this view, we present V3-crown directed broadly neutralizing Designed Ankyrin Repeat Proteins (bnDs) matching the breadth of V3-base bnAbs. While most bnAbs target prefusion Env, V3-crown bnDs bind open Env conformations triggered by CD4 engagement. BnDs achieve breadth by focusing on hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 124 publications
1
24
0
Order By: Relevance
“…Neutralization of HIV-1, or any other viral pathogen, minimally requires an initial encounter with an Ab. The PG9, PG16, and PGT145 mAbs can efficiently neutralize REJO virus (83), thus lack of detectable binding was unexpected, particularly since V3 is shielded only when the native Env trimer is in the closed pre-fusion conformation: a conformation that is required for the binding of V2q mAbs (99, 113).…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of HIV-1, or any other viral pathogen, minimally requires an initial encounter with an Ab. The PG9, PG16, and PGT145 mAbs can efficiently neutralize REJO virus (83), thus lack of detectable binding was unexpected, particularly since V3 is shielded only when the native Env trimer is in the closed pre-fusion conformation: a conformation that is required for the binding of V2q mAbs (99, 113).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that long and highly glycosylated V1 regions shield HIV-1 from recognition by V3-directed bNAbs ( Silver et al., 2019 ). V3-crown antibodies show exceptional potency and cross-reactivity in the absence of V1V2 shielding, indicating that distinct conformations of the HIV-1 V3 loop crown can be targeted for broad neutralization ( Friedrich et al., 2021 ). Fewer, or deletion of, PNGS in V1V2 suggested that the V3 loop may be selectively exposed and accessible on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…DARPins directed against the hetero-oligomeric macromolecular multiprotein complex, which comprises part of the baseplate of the phage could inhibit TP901-1 infection. Furthermore, the DARPin technology was employed to design HIV inhibitors targeting the envelope glycoprotein gp120 [ 72 , 73 ]. Broad neutralization could be achieved by a DARPin molecule directed to the V3 crown of HIV envelope glycoprotein gp120, providing relevant information for the development of novel antiviral strategies against HIV.…”
Section: Viral Applicationsmentioning
confidence: 99%